The effect of different shapes of shear keys at the interface of old and new concretes of jacketed RC column - Alam, M.; Sarker, Prabir; Rahman, M.; Himel, S. (Taylor & Francis Group, 2017)
This study aims to determine the effect of different shapes of shear keys at the interface of old and new concrete of jacketed RC column. Two types of shear keys such as: (i) straight shear keys; and (ii) one end hooked shear keys are used in this study. Concrete with compressive strength of 17.5 MPa and 24 MPa confirmed through mix design are taken into consideration to find out the effect of strength variation of concrete in column jacketing with different shear keys. A total number of twelve (12) Cement Concrete (CC) columns (six for 17.5 MPa concrete and six for 24 MPa concrete) were casted in the laboratory. All specimens were ensured curing for 28 days before carrying out surface treatment for jacketing. Outer surface of the columns was made rough by chipping through chisel. Thereafter, it was drilled up to a depth of 50 mm into the column using mechanical drill machine. Shear keys were inserted and bonded using cement paste into the drilled hole of the columns. Shear keys were placed at a space of 100 mm horizontally and vertically. After one day of fixing shear keys with columns, jacketing was performed with the same proportioned concrete as used to make the original column and kept in curing for 28 days. After jacketing, all columns dimensions were found as 250 × 250 mm (original column cross section is 150 × 150 mm). The length of the all columns was taken into consideration as 810 mm. These columns were tested under Universal Testing Machine (UTM) in the laboratory. Axial load carrying capacity and deformation were recorded during the test of all columns. It is observed that jacketed columns show more load carrying capacity and the deformation as well over the unjacketed columns. This increased load carrying capacity and deformations are found more for jacketed column with one end hooked shear keys. Interface bonding failures are found in jacketed column without shear keys and with straight shear keys. On the other hand, both jacketed concrete and old concrete are failed together for jacketed column with one end hooked shear keys. From this study it can be concluded that the jacketed columns with one end hooked shear keys perform better than the jacketed column without shear keys and straight shear keys for retrofitting/restrengthening of existing RC columns.